PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DAN AKTIVITAS BELAJAR SISWA KELAS VIII SMP NEGERI 3 PARIAMAN - LINDA GUSNITA (Jurnal Edukasi dan Penelitian Matematika, 2018)
Mathematical understanding consepts ability is one of purpose have must have by student in the learning mathematic. However to reality, student's mathematical understanding consepts ability grade VIII SMP 3 Pariaman not yet develop according to optimal. One of the way improve to it problem is with use cooperative learning model Think-Talk-Write (TTW) type. The aim of this study is to describe if student's mathematical understanding consepts ability acquire learning with cooperative learning model Think-Talk-Write type better than student acquire study with convensional model and how learning activity of student who study with cooperative learning model Think-Talk-Write type. This type of research is descriptive and quasi experiment. This instrument use is a mathematical understanding consepts ability test and student learning activity sheet. The conclusion based on the analysis of t test is student's mathematical understanding consepts ability acquire learning with cooperative learning model Think-Talk-Write type better than student acquire study with convensional. And learning activity of student increase. Keywords –Mathematical understanding consepts, Cooperative learning model Think-Talk-Write (TTW) type, Learning activtiy